Target-induced reconfiguration of DNA probes for recycling amplification and signal-on electrochemical detection of hereditary tyrosinemia type I gene. Issue 17 (7th September 2015) - Dou, Baoting; Yang, Cuiyun; Chai, Yaqin; Yuan, Ruo; Xiang, Yun
<x xml:space="preserve">Abstract</x> The presence of the target gene switches the dsDNA probes into active substrates for exonuclease III and leads to target recycling amplification for signal-on sensitive electrochemical detection of DNA.